2020
DOI: 10.3390/ijerph17186868
|View full text |Cite
|
Sign up to set email alerts
|

Estimation on Fixed-Bed Column Parameters of Breakthrough Behaviors for Gold Recovery by Adsorption onto Modified/Functionalized Amberlite XAD7

Abstract: The objective of this paper was to evaluate the potential of a new adsorbent material to recover Au (III) from real wastewater, in a column with a fixed bed in a dynamic regime. The material was obtained through functionalization, by impregnation of the commercial resin, Amberlite XAD 7 type, with L-glutamic acid, which has active groups –NH2 and –COOH. The goal of the experiments was to follow the correlation of fixed-bed column specific adsorption parameters (the effluent volume, the amounts of adsorbent, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The residual solutions resulting after the gold-plating procedure utilized in our research contained 2 g/L gold ions, 0.7-1 g/L Ni (II), 1 mg/L Cu (II), and 2 mg/L Fe (III), which were determined in these solutions before the experiments [44].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The residual solutions resulting after the gold-plating procedure utilized in our research contained 2 g/L gold ions, 0.7-1 g/L Ni (II), 1 mg/L Cu (II), and 2 mg/L Fe (III), which were determined in these solutions before the experiments [44].…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were carried out in triplicate, with standard deviations of the obtained values under 1%. In previous studies [44,50], the authors revealed more details of the experiments.…”
Section: Materials Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main weaknesses of the Thomas model is that its derivation assumes that the adsorption process is limited by kinetics, while it is often controlled by interphase mass transfer. Nevertheless, Thomas is widely used to describe the adsorption process in packed bed columns [37][38][39][40][41]. Furthermore, experimental data were also modelled with the Modified Dose Response (MDR) model [42]:…”
Section: Continuous Adsorption Testsmentioning
confidence: 99%